Clinical Indications of Hysterectomy in Gynecology Department of Ayub Teaching Hospital, Abbottabad - Fayaz, Khola; Bibi, Saima; Afridi, Sundus Ambreen; Batool, Fatima; Fayaz, Mahnoor; Imtiaz, Raheen (Indus Journal of Bioscience Research, 2025)
Background: Hysterectomy is one of the most commonly performed gynecological surgeries worldwide, indicated for a variety of benign and malignant conditions. Understanding the demographic and clinical profiles of women undergoing hysterectomy can help improve clinical decision-making and patient care. Objective: This study investigates the clinical indications of hysterectomy performed in Gynecology Department of Ayub Teaching Hospital, Abbottabad Materials and Methods: This cross-sectional study was conducted in the Gynecology Department of Ayub Teaching Hospital, Abbottabad, from 11th September 2024 to 12th March 2025. A total of 142 women who underwent hysterectomy were included. Data on age, parity, education, ethnicity, residence, and reproductive status were collected. The clinical indications for surgery were documented, and associations with age and menopausal status were assessed using the Chi-square test Results: The mean age of participants was 47.58 ± 9.4 years, with a mean parity of 4.96 ± 2.14. Most women were premenopausal (71.13%) and resided in rural areas (69.01%). The leading indication for hysterectomy was uterine fibroids (40.8%), followed by adenomyosis (23.2%), UV prolapse (11.97%), and endometrial hyperplasia (8.45%). A significant association was found between age and indications (p = 0.0198), with fibroids and adenomyosis more common in women over 40. Menopausal status also showed a significant association with indications (p = 0.00028). Conclusion: Uterine fibroids are the most common indication for hysterectomy, particularly among premenopausal women aged over 40. The indications for hysterectomy significantly vary with age and menopausal status, emphasizing the need for individualized treatment approaches.